Identifikasi Sesar Menggunakan Transformasi Pseudogravitasi Data Anomali Magnetik di Desa Pekuncen Kecamatan Jatilawang Kabupaten Banyumas - Sehah, Sehah; Raharjo, Sukmaji Anom; Sa'adah, Fajar Nur (Fakultas Teknik Geologi Universitas Padjadjaran, 2023)
Geophysical survey with magnetic method has been carried out in Pekuncen Village, Jatilawang District, Banyumas Regency. Magnetic data acquisition was carried out on 131 points using a set of Proton Precession Magnetometer (PPM) equipment. Data processing includes daily and IGRF corrections, reduction to a horizontal surface, and upward continuation. The application of pseudo-gravity transformation was carried out on magnetic anomalies data to clarify the sources of the magnetic anomalous which are the study target. Anomaly modeling was carried out along the AA' and BB' trajectories to identify the possibility of subsurface faults. Determination of the position of these trajectories is based on a pseudogravity anomaly contour map, especially to help determine the presence of faults. Based on the modeling results on the AA' trajectory, fault is found in sedimentary rock and basaltic rock; whereas in BB' trajectory, fault is found in basaltic rocks. Based on the modeling results, the maximum depth of the two faults is 500 m.